PHYTOCHEMICAL SCREENING AND ANTI-INFLAMMATORY EFFECT TEST OF ETHANOL EXTRACT OF TURMERIC RHIZOME (Curcuma domestica Val.)TOWARD MALE WHITE MOUSE (Rattus norvegicus) - Rulia Meilina (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2015)
Anti-inflammatory effect of ethanol rhizome of turmeric was conducted toward white mouse which is induced the carrageenan solution (lambda carrageenan) 1 %, research was conducted by dividing the animals into 5 groups.Group A was given CMC 0,5%, group B was given Indometacin with dose 100 mg/kgBB, group C was given  ethanol rhizome extract of turmeric with dose 400 mg/kgBB, group D was given ethanol rhizome extract of turmeric with dose 500 mg/kgBB, group E was given ethanol rhizome extract of turmeric with dose 600 mg/kgBB. Result of phytochemical screening toward powder and ethanol extract of rhizome of turmeric shows that chemical compounds which are involved are alkaloids, flavonoids, and aetheric oil. In the other hand, result of phytochemical screening toward ethanol extract of turmeric’s rhizome are alkaloids,flavonoids,anthraquinones, glycosides. Result of anti-inflammatory test shows that there is the real difference among groups of mouse which were given CMC suspension (control), suspension of ethanol extracts of turmeric’s rhizome with dose 400 mg/kg BB, 500 mg/kg BB, 600 mg/kg BB (material test) and suspension of indomethacin with dose 100 mg/kg BB (positive comparison). Suspension of ethanol extract of turmeric’s rhizome with dose 600 mg/kg BB shows that anti-inflammatory capability is better than dose 400 mg/kg BB and 500 mg/kg BB, and suspension of ethanol extract of turmeric’s rhizome dose 600 mg/kg BB shows the anti-inflammatory effect which is not really different with suspension of indomethacin with dose 100 mg/kg BB, it is showed by  ANOVA statistic analysis among those comparisons toward indomethacin suspension as positive comparison.Keywords:Anti-inflammatory, Indomethacin, Turmeric Rhizome